Chubby Infant – Should One Worry? An Infant with Primary lymphedema – Mini Review and Case Report - Kaczmarek, Joanna Magdalena; Graczykowska, Karolina Anna; Szymkuć-Bukowska, Iwona; Łoś-Rycharska, Ewa; Krogulska, Aneta (Klinische Pädiatrie, 2020)
Lymphedema is a localized form of tissue swelling, characterized by a progressive accumulation of a tissue fluid in the interstitial compartment as a result of the lymphatic system dysfunction. It is a rare disease in the pediatric population and in the majority of cases it is a consequence of an abnormal formation of the lymphatic system, which is called primary lymphedema. Although its epidemiology is not precise, it is assumed that 1:100 000 children suffer from primary lymphedema. The diagnosis can be made by a proper clinical examination after ruling out secondary causes of lymphedema, particularly in cases with a more asymmetric swelling of the extremities. In this very article we present a case report of an 8-months-old infant with primary lymphedema, who had presented swelling of the extremities from birth and yet no pathology was suspected before. The purpose of this article is to draw attention to the fact that a baby with excessive subcutaneous tissue is not always a healthy, chubby infant with considerable amount of fat tissue.Das Lymphödem ist eine lokalisierte Form des Gewebeödems, die durch eine fortschreitende Ansammlung von Gewebeflüssigkeit im Interstitialraum infolge einer Funktionsstörung des Lymphsystems gekennzeichnet ist. Dies ist eine seltene Erkrankung in der pädiatrischen Bevölkerung und in den meisten Fällen eine Folge der fehlerhaften Bildung des Lymphsystems, das als primäres Lymphödem bezeichnet wird. Obwohl die Epidemiologie nicht genau ist, wird angenommen, dass 1: 100 000 Kinder an einem primären Lymphödem leiden. Die Diagnose kann auf der Grundlage einer geeigneten klinischen Untersuchung gestellt werden, nachdem sekundäre Ursachen für Lymphödeme ausgeschlossen wurden, insbesondere bei asymmetrischeren Ödemen der Gliedmaßen. In diesem Artikel präsentieren wir den Fallbericht eines 8 Monate alten Kindes mit primärem Lymphödem, dessen Ödem der Gliedmaßen seit der Geburt aufgetreten ist, bei dem aber keine Pathologien vermutet wurde. Der Zweck dieses Artikels ist es, die Aufmerksamkeit auf die Tatsache zu lenken, dass ein Kind mit übermäßigem Unterhautgewebe nicht immer ein gesundes, molliges Kind mit übermäßigem Körperfett bedeutet.
Keywords: primary lymphedema; edema; infant; overweight